The association between length of emergency department boarding and hospital length of stay for patients with mental health and behavioural disorders - Hendrikse, Clint (Division of General Surgery, 2022)
Background Psychiatric boarding in Emergency Departments is a global challenge. Patients with mental and behavioural disturbances are disproportionally affected with boarding times up to three times longer than other patients. This retrospective cross-sectional study investigated the impact of an initiative to reduce psychiatric boarding on length of stay and readmission rate, as well as exploring the relationship between boarding times and length of stay. Methods All adult patients referred over a 24-month period (June 2017 – May 2019) for psychiatric admission from the Emergency Department of a Cape Town district hospital were included. This included a 9-month period prior to the initiative, after which inpatient capacity was increased, and inpatient hallway boarding was implemented. Data relating to admission processes and outcomes were extracted from electronic registries. Results In total, 2607 patients were referred for psychiatric admission (2.7% of all Emergency Department patients). The initiative was associated with a decrease of 95% (56 vs 3 hours, p24-hour boarding category (351 vs 360 hours, p=0.047). The readmission rate increased from 12% to 18% post intervention. Conclusion A significant improvement in hospital length of stay and psychiatric boarding times occurred after the initiative was implemented. The benefits should be weighed up against a subsequent higher readmission rate. From a lean- and economical perspective, the results of this study suggest that psychiatric boarding equates to waste as it is independent of ward length of stay. The observational nature of this study precludes concrete conclusions and further investigations into psychiatric inpatient hallway boarding are recommended.